Pediatric pulmonary actinomycosis: A misdiagnosed case report - Yilin, Zhao; Xinyi, Liu; Longwei, Sun; Hongwu, Zeng (Frontiers in Pediatrics, 2022)
Background Pulmonary actinomycosis is an uncommon kind of bacterial illness caused by actinomycetes, involving the chest wall in extraordinarily rare cases. Due to non-specific clinical signs and perplexing radiological characteristics, this kind of pulmonary actinomycosis is frequently misinterpreted as a malignant tumor or lung abscess. Case presentation An 11-year-old child presented with a palpable lump on his left chest and periodic chest discomfort. An irregular soft-tissue mass in the left upper zone with bony destruction was first identified as a malignant small round cell tumor (MSRCT) known as an Askin tumor on post-contrast CT. However, pathological biopsy of the pulmonary lesion through the chest wall revealed actinomycosis. Conclusion Pulmonary actinomycosis is an uncommon bacterial illness that has a variety of clinical manifestations, particularly in young patients. A chest lump with nearby “lace-like” rib bone destruction was the distinguishing characteristic of our case. For appropriate treatment and diagnosis, infection with actinomycosis should be considered when observing a similar chest lump. Pathological biopsy, as a valuable diagnostic tool, can help to distinguish between infectious diseases and thoracic tumors. The pathological manifestations of actinomycosis are characterized by inflammatory lesions that range from purulent to granuloma-like inflammatory processes, and second-generation sequencing of alveolar lavage fluid can help to confirm pathogens.